1978
DOI: 10.1111/j.1365-2265.1978.tb02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo‐pituitary‐gonadal Function in Male Central Precocious Puberty

Abstract: Eleven boys aged 1-10 years with central precocious puberty were studied. According to the pubertal development six were classified as P2, one as P3 and four as P5. In all cases plasma testosterone levels were definitely elevated (1.7-5.8 ng/ml) when compared with pre-pubertal controls. Peak values after HCG (3 X 1500 units) in four of the boys were in the high adult range. The binding capacity of serum testosterone oestradiol binding globuline (TeBG) ranged between 0.5 and 7.30 microgram/dl. Basal plasma leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…CPP is considered to be organic when it is associated with a lesion of the central nervous system (CNS), and as idiopathic when the computed tomography (CT) or magnetic resonance imaging (MRI) show no associated lesion of the central nervous system. The incidence of idiopathic forms and the pattern of development of CPP vary according to gender (Sigurjonsdottir & Hayles, 1968; Chaussain et al ., 1978; Cacciari et al ., 1983; Cutler, 1990; Kaplan & Grumbach, 1990; and Oerter et al ., 1990). Idiopathic CPP is rare in boys (fewer than 30% of CPP cases), while the opposite is true for girls (up to 80% of CPP cases).…”
mentioning
confidence: 99%
“…CPP is considered to be organic when it is associated with a lesion of the central nervous system (CNS), and as idiopathic when the computed tomography (CT) or magnetic resonance imaging (MRI) show no associated lesion of the central nervous system. The incidence of idiopathic forms and the pattern of development of CPP vary according to gender (Sigurjonsdottir & Hayles, 1968; Chaussain et al ., 1978; Cacciari et al ., 1983; Cutler, 1990; Kaplan & Grumbach, 1990; and Oerter et al ., 1990). Idiopathic CPP is rare in boys (fewer than 30% of CPP cases), while the opposite is true for girls (up to 80% of CPP cases).…”
mentioning
confidence: 99%
“…CPP before the age of one year is exceedingly rare, even among patients with organic forms related to brain tumors and/or malformations. Chaussain et al [ 25 ] reported that among the 10 boys with CPP (only one idiopathic aged 10.5 yr), the 3 younger than one year included two boys with tumors of the 3 rd ventricle and one with ventricular dilatation; all had pubertal concentrations of testosterone. Rivarola et al [ 26 ] reported that among the 30 patients with CPP and organic central lesions, 3 were younger than one year and had hypothalamic hamartoma, germinoma or suprasellar arachnoid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…FSH and sexual steroid levels as also gonadotropin response to LHRH are of the postpubertal type [4]. The most common pathological processes of the central nervous system which cause a precocious puberty are: hypothalamic hamartomas, astrocytomas of the hypothalamo-chiasmatic area, tumors of the pineal region, ectopic pinealomas, tumors of the anterior part of the third ventricle, teratomas and suprasellar germinomas.…”
mentioning
confidence: 99%